Examining Extreme Rainfall Forecast and Communication Processes in the South Central United States - Wanless, Anna (My University, 2021)
Extreme rainfall events have increased in parts of the United States and climate models project that trend to continue (Carter et al. 2018; Mullens et al. 2013; Hayhoe et al. 2018). As such, forecasters must be able to effectively communicate the potential threats and impacts associated with these events to their users. How National Weather Service (NWS) meteorologists and hydrologists communicate with their audiences leading up to and during extreme rainfall events has not yet been widely explored. This study aims to help address that knowledge gap. This research investigated how NWS forecasters processed and communicated information about extreme rainfall events that occurred in the South Central U.S. between 2015 and 2019. An event was included in this study if the NWS Hydrometeorological Design Studies Center determined it to have an Annual Exceedance Probability of 1/500 or less in one of their storm analyses. Nine events were identified. Semi-structured interviews were conducted with 21 NWS forecasters about their experiences with the events and how they or their offices messaged the event(s). Study participants were asked event-specific questions about products disseminated by their offices leading up to and during the event(s) and how they internally processed and externally communicated model outliers and anomalous rainfall events overall. Interviews also explored forecasters’ perceptions of the relationship between these events and climate change and if those perceptions impacted the forecasts and messaging for the event. Using deductive qualitative analysis, components of sensemaking (Weick et al. 2005; Butterworth 2010; and Doswell 2004) and decision-making (Millet et al. 2020) conceptual frameworks as well as principles of forecasting (Armstrong 2001b) were identified in the responses. A simple forecast communication process model was created to illustrate the findings. While the forecast and communication processes are complex and vary between offices and forecasters, these frameworks and the process model provide a high-level understanding of how forecasters translate their knowledge to usable information for their audiences. With an awareness of the purpose of the forecast, forecasters use sensemaking and decision-making frameworks to process data from models and observations. These processes are impacted by forecast uncertainty, which will always be present but is challenging to convey. Then, forecasters consider what sensemaking and decision-making processes their audiences will go through as they try to understand the forecast information. These principles and frameworks then impact how they present the forecast to their audiences. The study also found that forecasters do not consider the impacts climate change might have on an extreme rainfall event when forecasting such an event. However, climate change is something that they may consider when reflecting on the event after it occurred.
Keywords: Meteorology; Atmospheric Science; Weather Forecasting; Forecast Communication